The Influence Of Work Evaluation, Pension Fund Expectations, and Non-Financial Rewards On The Professional Behavior Of Teachers - Juana, Syafri; Mukhtar; Kemas Imron Rosadi (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study examines the direct and indirect effects of Job Evaluation, Pension Fund Expectations, and Non-Financial Rewards on Teachers' Professional Behavior. Using an associative quantitative approach with a survey design, the research was conducted at MAN 1 Tanjung Jabung Barat, MAN 2 Kota Jambi, and MAN 1 Kerinci. The study population includes 794 ASN teachers in State Madrasah Aliyah (MAN) in Jambi Province, consisting of 568 civil servant teachers (PNS) and 226 government contract teachers (PPPK). The sample was purposively selected, comprising 24 teachers from MAN 1 Tanjung Jabung Barat, 62 teachers from MAN 2 Kota Jambi, and 36 teachers from MAN 1 Kerinci. The results indicate that Job Evaluation directly influences Teachers' Professional Behavior, contributing 75.44%, while Pension Fund Expectations contribute 69.26%. Simultaneously, both variables have a combined effect of 79.59%. Job Evaluation and Pension Fund Expectations also impact Non-Financial Rewards by 55.49% and 56.72%, respectively, and jointly by 73%. Non-Financial Rewards directly influence Teachers' Professional Behavior, contributing 64.89%. The simultaneous effect of all three variables on Teachers' Professional Behavior reaches 79.68%. Furthermore, Job Evaluation and Pension Fund Expectations, through Non-Financial Rewards, contribute 53.6% and 56.11%, respectively. These findings highlight the importance of job evaluation, financial incentives, and non-financial rewards in enhancing teachers' professionalism.